Further Validation of Learning Outcome Assessment Instruments on Occupational Safety & Health (K3/OSH) for Students of Building / Civil Engineering - Endroyo, Bambang; Buntoro Wahjono, Harijadi Guwawan; Chairunnisa, Ashri; Aprimiana, Felita (Journal of Vocational and Career Education, 2020)
At present and in the future, the existence of a universty, beside fill in to the predetermined conditions is also assessed by how much graduates enter the world of work. Therefore, universities must accommodate themselves. The important unit of a university is a department, including the Department of Civil Engineering, in Universitas Negeri Semarang (UNNES). Industry-oriented learning enhancement, one of which is the assessment of learning outcomes for subjects must also be developed. This study develop an instrument for assessing learning outcomes in the K3/OSH subject in the Civil Engineering Department of UNNES. The existing learning outcome instruments need to be more developed so that they are not too theoretically but more industry-oriented, in the realms of knowledge, attitudes, and psychomotor. Continuous improvement needs to be done because the material learning that must be adapted to the industry that always evolving. Apart from the above, UNNES also has a vision of conservation with environmental preservation as one of its focus. Conservation values must also be included in the instrument. The next issue is corona pandemic. Students must be assessed in knoweldge of work in pandemic eventhough he or she know from out of class. Through the development of these instruments, it was hoped that the Civil Engineering Department of UNNES can play a more real role in both the world of education and the world of work (construction).